'We have goals but [it is difficult]'. Barriers to antiretroviral therapy adherence among women using alcohol and other drugs living with HIV in South Africa - Jacqueline W. Ndirangu; Margaret W. Gichane; Felicia A. Browne; Courtney P. Bonner; William A. Zule; Erin N. Cox; Kevin M. Smith; Tara Carney; Wendee M. Wechsberg (Wiley, 2022)
Abstract Background Women living with HIV who misuse alcohol and live in economically disadvantaged settings in South Africa experience a multitude of contextual barriers as they navigate the HIV care continuum. The Women's Health CoOp (WHC), a brief, woman‐focused, behavioural, evidence‐based intervention, has been shown to be effective in reducing heavy drinking and improving HIV‐related outcomes among this key population. However, these women face other broader socioecological barriers to antiretroviral therapy (ART) adherence. Methods The WHC was implemented in a modified, stepped‐wedge implementation science trial in public health clinics and substance use treatment programmes in Cape Town, South Africa. A qualitative substudy was conducted to explore barriers to HIV treatment adherence among women enrolled in this trial. Eight focus group discussions were conducted with 69 participants 6 months after completion of the WHC workshops. Focus groups were audio‐recorded (with consent), transcribed verbatim and analysed using a thematic approach. Results The mean age of the participants was 33 years and the mean self‐reported number of drinks per day was 13. The main contextual factors influencing participants' ART adherence were intrapersonal‐level factors (substance use, financial constraints, food insecurity; community‐level factors (anticipated and enacted stigma, community violence) and institutional‐level factors (patient-provider relationships, health facility barriers, environmental stigma). Conclusion Comprehensive interventions addressing the contextual barriers and unique challenges faced by women who misuse alcohol in low‐resource settings that intersect with HIV treatment nonadherence should be implemented in tandem with successful biobehavioural HIV interventions for long‐term effectiveness and sustainability. Patient or Public Contribution Our South African community collaborative board has been involved throughout this study; participants and clinic staff voices have been essential in our interpretation of these findings.